2005
DOI: 10.1016/j.febslet.2005.09.076
|View full text |Cite
|
Sign up to set email alerts
|

Novel type aquaporin SIPs are mainly localized to the ER membrane and show cell‐specific expression in Arabidopsis thaliana

Abstract: We investigated the fourth subgroup of Arabidopsis aquaporin, small and basic intrinsic proteins (SIPs). When they were expressed in yeast, SIP1;1 and SIP1;2, but not SIP2;1, gave water-channel activity. The transient expression of SIPs linked with green fluorescent protein in Arabidopsis cells and the subcellular fractionation of the tissue homogenate showed their ER localization. The SIP proteins were detected in all of the tissues, except for dry seeds. Histochemical analysis of promoter-b-glucuronidase fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(148 citation statements)
references
References 34 publications
2
145
0
1
Order By: Relevance
“…Similar to what was observed in pollen, we detected a consistent, intracellular PIN8-GFP signal co-localized with ER markers, such as BIP2 (ref. 28) in root cells ( Fig. 3d-f, p).…”
Section: Pin8 Is Expressed and Functions In The Male Gametophytementioning
confidence: 90%
“…Similar to what was observed in pollen, we detected a consistent, intracellular PIN8-GFP signal co-localized with ER markers, such as BIP2 (ref. 28) in root cells ( Fig. 3d-f, p).…”
Section: Pin8 Is Expressed and Functions In The Male Gametophytementioning
confidence: 90%
“…subfamily), and it has been suggested that they are glycerol (MIP1) or water and glycerol (MIP2) transporters. MIP3 exhibits the greatest similarity to plant small basic intrinsic proteins (SIPs) (31), which generally are localized in the plant endoplasmic reticulum (ER) membrane (32). MIP1 and MIP3 were readily detected using reverse transcription-PCR, indicating that MIP2 is expressed only weakly, if at all, in our culture conditions.…”
Section: Osmoregulation Inmentioning
confidence: 90%
“…We compared the fluorescent patterns of various markers (Figures 5A to 5G; see Supplemental Movie 1 online) with that of CHX23-GFP ( Figure 5H; see Supplemental Movie 2 online) and found that the CHX23-GFP signal was similar to that of an ER membrane-bound protein, SIP2. 1-GFP (Ishikawa et al, 2005) (Figure 5E), and an ER lumen protein, GFP-HDEL ( Figure 5F; see Supplemental Movie 1 online). To verify this possibility, tobacco pollen was cotransfected with CHX23-RFP and SIP2.1-GFP or GFP-HDEL.…”
Section: Chx23 Is Localized To Endomembranes Resembling Er In Growingmentioning
confidence: 99%
“…For each bombardment, 1.25 mg DNA and 7 mg tobacco pollen were used. Pollen was transfected with NtPLIM2b-GFP , GFP-Rab2 , GFP-Rab5, mito-GFP, GFP-HDEL (Cheung and Wu, 2007), SIP2.1-GFP (Ishikawa et al, 2005;A. Cheung and H. Wu, unpublished data), and LAT52:GFP (Cheung, 2001) to visualize actin filament, Golgi, endosome, mitochondria, ER, and cytosol, respectively.…”
Section: Plant or Pollen Transformationmentioning
confidence: 99%